2022
DOI: 10.1080/02770903.2022.2123742
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and quality of life in children with well-controlled asthma

Abstract: We would like you to answer some questions about how you have been feeling during the past four weeks. Please answer all the questions if you can. If you don't understand a question or would prefer not to answer it, please leave it out and go on to the next one.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Furthermore, a reduction in the need for daily medication was reported by the children who were regularly engaged in physical activity, again in agreement with previous reports [ 11 ]. Moreover, among physically inactive children with asthma, others also have reported poorer quality of life [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a reduction in the need for daily medication was reported by the children who were regularly engaged in physical activity, again in agreement with previous reports [ 11 ]. Moreover, among physically inactive children with asthma, others also have reported poorer quality of life [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on subjective methods of assessment, Gianfrancesco et al [12] observed that 26% of children with asthma were classified as 'inactive' vs. 14% of children without asthma, when utilising the International Physical Activity Questionnaire (IPAQ). Likewise, Preftoulido et al [20] reported that only 3% of children with asthma meet 'satisfactory' activity levels (86% classified as sedentary) according to the Godin Leisure-Time Exercise Questionnaire.…”
Section: Physical Activity Profiles In People With Asthmamentioning
confidence: 99%
“…However, it is important to acknowledge that a significant portion of the population, particularly in highly developed countries, lack sufficient physical activity and instead have sedentary lifestyles [19]. These sedentary habits, combined with improper eating habits, or even mental illnesses, contribute to childhood diseases such as obesity, diabetes, and asthma [20][21][22]. On the contrary, engaging in nautical activities such as sailing increases students' confidence and competence, key personal and interpersonal skills, life-specific skills, specific navigation skills, physical fitness, and overall mental well-being [23].…”
Section: Introductionmentioning
confidence: 99%